(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Any debate over participatory development and good governance is inseparable from the end of the Cold War, the lost decade of the 1980s, and evolving discussions over development strategies from the economic growth orientation of the 1950s to the structural adjustment and sustainable development of the 1980s. Since the Cold War’s end, donor countries have come to demand that development aid be more effectively and efficiently implemented and started to seek new aid strategies capable of garnering the support of their people and of replacing the strategy based on East-West ideological conflict. There is growing awareness that in order for aid to have visible effects, to protect human rights, and to promote democratization, donors must become actively involved in reforms of developing nations’ political systems, policies, and implementing structures. Keywords Development, Participation, Economic